2007
DOI: 10.1074/jbc.m700660200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of an NH2-terminal Disease-causing Mutation Hot Spot to the “Clamp” Region in the Three-dimensional Structure of the Cardiac Ryanodine Receptor

Abstract: A region between residues 414 and 466 in the cardiac ryanodine receptor (RyR2) harbors more than half of the known NH 2 -terminal mutations associated with cardiac arrhythmias and sudden death. To gain insight into the structural basis of this NH 2 -terminal mutation hot spot, we have determined its location in the three-dimensional structure of RyR2. Green fluorescent protein (GFP), used as a structural marker, was inserted into the middle of this mutation hot spot after Ser-437 in the RyR2 sequence. 2؉ rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 39 publications
4
65
2
Order By: Relevance
“…Our confidence in placement of the density corresponding to the N terminus of RyR1 within the cryo-EM map is substantiated by previous difference imaging with GST-RyR and GFP-RyR fusion proteins and antibody labeling ( Fig. S5) (25)(26)(27). Model placement is further validated by the match of the ␤-sheets ␤5 and ␤6 and a long helix (␣9) independently derived from the aforementioned SSEHunter results (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Our confidence in placement of the density corresponding to the N terminus of RyR1 within the cryo-EM map is substantiated by previous difference imaging with GST-RyR and GFP-RyR fusion proteins and antibody labeling ( Fig. S5) (25)(26)(27). Model placement is further validated by the match of the ␤-sheets ␤5 and ␤6 and a long helix (␣9) independently derived from the aforementioned SSEHunter results (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…The first 210 amino acids of the RyR1 structure (rabbit) was at 2.5 Å resolution (PDB ID code 3HSM) (Amador 2009), and a similar fragment (amino acids 9 -205 of rabbit RyR1) was resolved at 2.9 Å resolution (PDB ID code 3ILA) (Lobo and Van Petegem 2009). The structure of the first 217 amino acids of mouse RyR2 was at 2.5 Å resolution (PDB ID code 3IM5) (Lobo and (Wang et al 2007) and was mapped to a location between subdomains 5 and 9 using green fluorescent protein insertion into the primary structure and difference mapping of cryo-EM reconstructed structures (Wang et al 2007). Notably, mutations at positions Glu161, Arg164, Arg402, and Ile404 of RyR1 and the mutations Arg169, Ile417, and Arg418 of RyR2 are located in the suggested FKBP binding pocket (Serysheva et al 2008); whereas the Ile4898Thr CCD mutation appears to be located in the proposed selectivity filter in the pore region.…”
Section: Crystal Structure Of the Amino-terminal Domainmentioning
confidence: 99%
“…At 30 Å resolution, the structures of the three RyR subtypes are almost indistinguishable, and because they, like the three subtypes of IP 3 R, share about 65% sequence identity, it seems reasonable to suppose that the 3D structures of all IP 3 R are also likely to be similar to each other. These studies of RyR have identified positions of critical residues within the 3D structure, the sites to which accessory proteins bind, and conformational changes associated with opening of the pore (Orlova et al 1996;Serysheva et al 2005;Wang et al 2007;Jones et al 2008). Activation of RyR is associated with considerable changes in both the pore and cytoplasmic regions: The four corners of the latter dip down toward the SR, while the central region lifts away from it (Samso et al 2009).…”
Section: Structural Determinants Of Ip 3 R Activationmentioning
confidence: 99%
“…Such an interaction would require that the SD comes very close to the pore, but the exact location of the SD within the 3D structure of either the IP 3 R or RyR is unknown. The N-terminal of the RyR probably lies within the clamp region at the periphery of the large square cytoplasmic structure (Wang et al 2007), and it does change shape during RyR activation (Samso et al 2009). Yet, in this location the N-terminal is too far from the pore to interact directly with the TMD4-5 loop, consistent perhaps with evidence that in RyR the N-terminal may interact directly with a neighboring domain that includes residues from the central part of the primary sequence (Wang et al 2007).…”
Section: Structural Determinants Of Ip 3 R Activationmentioning
confidence: 99%
See 1 more Smart Citation